Statistical aspects on the usage of some dermatological creams with metallic nanoparticles - CHIOREAN, Ioana (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The main purpose of the present paper is to emphasize, by statistical studies, the anti-inflammatory effect of some new prepared nanomaterials on skin diseases (psoriasis). These new materials are based on silver and gold nanoparticles and natural compounds extracted from native plants of Adoxaceae family (European Cranberry Bush - Viburnum opulus L., European black Elderberry - Sambucus nigra L. and Cornus mas), which grow in our country and possess a known anti-in ammatory activity mainly due to their high content of anthocyanins and other polyphenols. Mathematics Subject Classification (2010): 62P10.